Legal aspects of finance in emerging markets - Ajayi, Olaniwun (Durban, South Africa LexisNexis Butterworths, 2005)
The book is a collection of essays of great quality and variety on virtually every aspect of financing, international commercial contracting and dispute resolutions in Nigeria.. it is comprehensive practical and scholarly.
Includes index
opc 30/12/16
Loans
Keywords: Finance - Law; Legal aspect - finance; Legal aspect - emerging market